Bioengineering strategies to generate artificial protein complexes. Issue 8 (19th May 2015) - Kim, Heejae; Siu, Ka‐Hei; Raeeszadeh‐Sarmazdeh, Maryam; Sun, Qing; Chen, Qi; Chen, Wilfred
ABSTRACT For many applications, increasing synergy between distinct proteins through organization is important for the specificity, regulation, and overall reaction efficiency. Although there are many examples of protein complexes in nature, a generalized method to create these complexes remains elusive. Many conventional techniques such as random chemical conjugation, physical adsorption onto surfaces, and encapsulation within matrices are imprecise approaches and can lead to deactivation of protein native functionalities. More "bio‐friendly" approaches such as genetically fused proteins and biological scaffolds often can result in low yields and low complex stability. Alternatively, site‐specific protein conjugation or ligation can generate artificial protein complexes that preserve the native functionalities of protein domains and maintain stability through covalent bonds. In this review, we describe three distinct methods to synthesize artificial protein complexes (genetic incorPoration of unnatural amino acids to introduce bio‐orthogonal azide and alkyne groups to proteins, split‐intein based expressed protein ligation, and sortase mediated ligation) and highlight interesting applications for each technique. Biotechnol. Bioeng. 2015;112: 1495–1505. © 2015 Wiley Periodicals, Inc.